Towards future-oriented innovation management: expert knowledge creation in foresight workshops - Dufva Mikko; Ahlqvist Toni (Korea, Republic of (South Korea), 2022)
Foresight is one way to cope with the challenges of unfamiliar or unpredictable situations and diverse viewpoints that innovation management nowadays faces. Many foresight exercises use workshops. In this article we are interested in what types of knowledge there are in a foresight workshop process and how these types of knowledge are created, shared and synthesized. Our goal is to both improve the theoretical understanding of knowledge creation about the futures in participatory settings and provide a framework for practitioners to better plan foresight workshops. We argue that there are two competing rationales in foresight: a divergent futures rationale and a convergent managerial rationale. We propose four knowledge types relevant for foresight workshops and a conceptual model of a workshop process and illustrate these with two workshop sessions.
The 5th Innovation Symposium – Stimulating Innovation: Challenges for Management, Science & Technology